(untitled) (Research, Society and Development, 2021)
The aim of this study was to investigate the main therapeutic regimens used so far in the Covid-19 fight on the world stage. Is a systematic literature review conducted in ScienceDirect, Literatura Latino-Americana e do Caribe em Ciências da Saúde (Lilacs) and Scientific Electronic Library Online (SciELO) databases, using the term “treatment Covid-19”, carried out in April 2020. We selected 16 articles according to the inclusion criteria: research articles, published between February 2019 and April 2020, without distinction of languages. The work was organized according to PRISMA recommendations, registered in PROSPERO. The articles found, ranged from in vitro, in silico, open clinical trials, cohort, retrospective and analytical, and were conducted in China, France, India, Saudi Arabia and South Korea, with the highest number of Chinese publications (70.5%). Samples range from one to 199 people, all infected with the SARS-CoV-2 virus, with a higher percentage of females (51.7%), ages 18 to 88 years. Medicines like lopinavir, ritonavir, favipiravir, arbidol, costicoteroids, hydroxychloroquine, recipes of traditional Chinese medicine, glycirrizine, azithromycin, and tocilizumab were analyzed in studies in a monotherapeutic or associated form, as well as mesenchyhimsal stem cell transplantation, intensive plasma exchange and intravenous immunoglobulin. There were divergences and complementation of results among the authors. Despite presenting findings and assisting in the fight against the pandemic, current studies present promising drugs for the treatment of symptomatology and viral load, with the objective of identifying an ideal treatment for the disease, not obtaining consensus.